2018
DOI: 10.1001/jamasurg.2017.3151
|View full text |Cite|
|
Sign up to set email alerts
|

Management of Stage I Squamous Cell Carcinoma of the Anal Canal

Abstract: IMPORTANCE The incidence of squamous cell carcinoma of the anal canal (SCCAC) is increasing. Although standard management of SCCAC includes the use of concurrent chemotherapy and radiotherapy (chemoradiotherapy), data are lacking on potentially less morbid, alternative management strategies, such as local excision, among patients with node-negative T1 disease. OBJECTIVES To examine the use of local excision among patients with T1 SCCAC and to compare overall survival relative to those who received standard tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 27 publications
2
44
0
1
Order By: Relevance
“…High locoregional failure rates were also reported by Goldman et al [10], in four out of seven (57%) patients treated with APR alone and in seven of nine (78%) patients treated with local excision alone for a stage T1-2N0 cancer in the anal canal. In a more recent study [14] based on the National Cancer Database, 2243 patients with stage T1N0 SCCA localized in the anal canal were analyzed. Five hundred and thirteen patients were treated with local excision alone and the remaining 1740 patients received CRT.…”
Section: Discussionmentioning
confidence: 99%
“…High locoregional failure rates were also reported by Goldman et al [10], in four out of seven (57%) patients treated with APR alone and in seven of nine (78%) patients treated with local excision alone for a stage T1-2N0 cancer in the anal canal. In a more recent study [14] based on the National Cancer Database, 2243 patients with stage T1N0 SCCA localized in the anal canal were analyzed. Five hundred and thirteen patients were treated with local excision alone and the remaining 1740 patients received CRT.…”
Section: Discussionmentioning
confidence: 99%
“…If located in the anal canal, LE carries a risk of sphincter damage and is therefore relatively contraindicated. Nevertheless, a recent retrospective cohort study of the US National Cancer Database on 2243 cases with T1 N0 SCCA has shown that over the period 2004-2012 LE was increasingly used in the more recent years, also for tumors of the anal canal [73]. Although criticized for its lack of information on the exact tumor location, LRC and DFS [74,75], this study and the Australian survey [71] illustrate that clinicians are reluctant to treat these small tumors with standard CRT.…”
Section: Curative Local Excisionmentioning
confidence: 87%
“…Excision alone of small anal/perianal cancers has had variable success, 19 , 20 , 22 , 23 but the use of EO is rising. 5 A population study of EO vs CRT showed reduced survival for EO after 80 months, despite the early stage; however, LR was not measured. 22 …”
Section: Discussionmentioning
confidence: 99%
“… 1 Serendipitous excision of anal canal (AC) T1 ASCC can occur with some evidence of noninferior outcomes to CRT. 5 Nonetheless, EO remains controversial 6 and a prospective UK study is underway. 7 Patients with inadequate excision margins and those with greater than stage T1N0 disease are treated with adjuvant CRT.…”
mentioning
confidence: 99%